MANAJEMEN BOARDING SCHOOL DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA DI SMP ISLAM INTEGRAL LUQMAN AL HAKIM KUDUS - Zusron, Wifaqul Azmi; Bakhri, Syaiful (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Boarding school is a social institution that focuses on building the character of students, which functions as a companion to formal education at school. Dormitory-based education systems such as boarding schools, especially those based on Islamic values, make school principals and teachers more intensive in teaching and instilling character values in students. This research approach uses qualitative descriptive research. Data collection techniques use several methods, namely observation, interviews and documentation. Data analysis techniques use data reduction methods, data presentation and drawing conclusions. The results of the research show that: 1) Planning for boarding school management at Luqman Al Hakim Kudus Integral Islamic Middle School goes through several stages, namely determining the purpose of having a dormitory by uniting the vision and mission of the dormitory, determining human resources by means of a teacher/religious teacher recruitment system, develop programs with daily life applications. 2) Implementation of boarding school management at the Luqman Al Hakim Kudus Integral Islamic Middle School is carried out by creating a predetermined daily activity schedule for students, building students' character by following programs in the dormitory, drawing up rules and regulations so that the students obey. 3) Evaluation of boarding school management at SMP Isalm Integral Luqman Al Hakim Kudus was carried out divided into two evaluations. The first is an evaluation of the students, such as providing punishment/sanctions for students who violate them, achieving the target of depositing the students' Qur'an memorization, recapping the daily results of the students with the exams they take, then making it into one book, namely a report card.